Experimental research and mechanical analysis on the bond‐slip behavior between concrete and corroded I‐shaped steel. (31st March 2021) - Zhang, Yiteng; Wang, Mingnian; Yu, Li; Guo, Xiaohan; Liu, Kerui; Yang, Henghong
Abstract: Corrosion of I‐shaped steel in the primary support of the subsea tunnel is inevitable due to high chloride ion content, which will weaken the bond performance between concrete and I‐shaped steel, resulting in a reduction in the service time of the subsea tunnel. Based on Xiang'an subsea tunnel, the bond–slip behavior between concrete and corroded I‐shaped steel was studied by the accelerated corrosion tests and push‐out tests, the experimental results indicated that: (1) The cracks of experimental specimens could be divided into two main forms: splitting failure (corrosion rate less than 5.79%); spalling failure (corrosion rate more than 5.79%). (2) A three‐stage bond‐slip law for concrete and corroded I‐shaped steel was proposed, and the formulae for calculating the bond strength were established. Furthermore, the degradation process of bond‐slip caused by corrosion was analyzed by energy principle and damage mechanics. Based on energy principle, it found that the elastic energy stored in the interface increased before the peak point of bond‐slip curve and decreased after the peak point, while the dissipated energy in the interface always increased with slip value. Finally, the interface relative damage variable was defined based on secant line anti‐sliding modulus and slip equivalent principle. The interface damage development process can be divided into three stages: initial damage, rapid damage development, and slow damage accumulation.